2016
DOI: 10.1016/j.ijheatfluidflow.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study on droplet-particle collision dynamics

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version.Permanent repository link: http://openaccess.city.ac.uk/15666/ Link to published version: http://dx. AbstractThe impact of liquid droplets onto spherical stationary solid particles under isothermal conditions is simulated. The CFD model solves the Navier-Stokes equations in three dimensions and employs the Volume of Fluid Method (VOF) coupled with an adaptive local grid refinement technique abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Using this technique, the grid is refined close to the liquid-gas interface and follows its motion dynamically, while the computational cost is decreased compared to a uniform grid having the same resolution [33]. The current model, has been validated for droplet impact onto solid flat and spherical surfaces under isothermal conditions [33,34]; in this work it is extended to account for heat transfer, phase change and surface "cracking" reactions, as will be presented in the following sections.…”
Section: Fluid Flow and Volume Of Fluid Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this technique, the grid is refined close to the liquid-gas interface and follows its motion dynamically, while the computational cost is decreased compared to a uniform grid having the same resolution [33]. The current model, has been validated for droplet impact onto solid flat and spherical surfaces under isothermal conditions [33,34]; in this work it is extended to account for heat transfer, phase change and surface "cracking" reactions, as will be presented in the following sections.…”
Section: Fluid Flow and Volume Of Fluid Methodsmentioning
confidence: 99%
“…It was observed that as the temperature of the catalyst increases or the initial drop kinetic energy decreases, the gas layer is formed more easily, and therefore the possibility of liquid pore blockage decreases. Another way to estimate solid-liquid contact would be to measure the percentage of wall area which is actually covered in liquid as in [34]. Finally, the best/worst case scenarios refer only to the operating conditions investigated.…”
Section: Dtp=2mentioning
confidence: 99%
“…The liquid film was easily to splash during the coating process when the impact velocity was high. The liquid film splashed at some point and the inner part of the liquid film retracted under the surface tension while the outer part of the liquid film continued to spread and gathered in the bottom as a long strip [27].…”
Section: The Effect Of Impact Velocitymentioning
confidence: 99%
“…If the spherical diameter was much larger than the droplet diameter, the impact effect was similar to the impact on a plate [30]. Malgarinos et al [27] indicated that coating would take place when the droplet initial kinetic energy was equal or higher than the surface energy needed to spread the film past the particle equator. Besides the rate of film thinning became slower with decreasing curvature ratio (the ratio of the initial droplet diameter to the surface diameter).…”
Section: The Effect Of Curvature Ratiomentioning
confidence: 99%
“…For the latter cases, the bubble density obeys a polytropic gas equation of state ( ), where the constant parameter κ is set according to a reference state for gas pressure and density. The thermal VOF model has been extensively used in a number of studies from the authors' group in deforming droplet simulations such as in [10][11][12] and in [13][14][15], but also in cases with polytropic bubble dynamics as in [16,17]. The model equations have been presented in detail in the aforementioned works and thus they are not repeated here.…”
Section: Mathematical Modelsmentioning
confidence: 99%